Possibility of cultivation gray mangroves Avaccinnia marina (Forsk.) Vierh. in the Iraqi coasts - Alrubaye, Aymen A.L.; Al-Zewar, Jihad M.; Al-Aradi, Haleemah J.; Qasim, Audai MH. (Iraqi Journal of Aquaculture, 2023)
A team from Marine Science Centre/ University of Basrah, in cooperation with some regional and local scientific institutions, attempted to cultivate the mangrove Avicennia marina in some Iraqi coastal areas, as part of an experiment that is the first of its kind in the country. A site was chosen to plant these trees in the tidal zone in the Khor Al-Zubair oil port. After six months of seedling growth in the greenhouse, the seedlings were transferred to the test site, and measurements of plant growth indicators were carried out for two years at the test site for the period from April 2019 to April 2021. The maximum height of the plants during the study period was 173.3 cm, while The indicators of vegetative growth and chlorophyll content increased significantly during the study period, which is close to the growth of trees in their natural habitats. The survival rates of seedlings were 44% after 24 months of planting. Most of the results were compared according to the Least Significant Difference test (L.S.D.). At a probability level of 0.05.